The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12012-011-9140-0
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Flavonoid-Rich Eugenia jambolana Seed Extract Retards In Vitro and In Vivo LDL Oxidation and Expression of VCAM-1 and P-Selectin in Atherogenic Rats

Abstract: The present inventory evaluates anti-atherogenic potential of flavonoid-rich Eugenia jambolana seed extract (EJSE) against in vitro low-density lipoprotein (LDL) oxidation, foam cell formation, and atherogenic (ATH) diet-induced experimental atherosclerosis in rats. EJSE was able to prevent in vitro LDL oxidation and oxidized LDL-induced macrophage foam cell formation. Also, EJSE supplementation to ATH rats significantly minimized increment in serum markers of LDL oxidation. The ex vivo oxidation indices were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…3). These observations are in accordance with our previous studies wherein, flavonoid and polyphenol rich herbal extracts have been reported to prevent ApoB fragmentation of Ox-LDL samples Jadeja et al 2011Jadeja et al , 2012. The ox-LDL induces pro-inflammatory changes in vascular endothelium and macrophage mediated uptake of ox-LDL transforms them into "lipid laden" foam cells (Steinberg 1997).…”
Section: Resultssupporting
confidence: 93%
“…3). These observations are in accordance with our previous studies wherein, flavonoid and polyphenol rich herbal extracts have been reported to prevent ApoB fragmentation of Ox-LDL samples Jadeja et al 2011Jadeja et al , 2012. The ox-LDL induces pro-inflammatory changes in vascular endothelium and macrophage mediated uptake of ox-LDL transforms them into "lipid laden" foam cells (Steinberg 1997).…”
Section: Resultssupporting
confidence: 93%
“…34 These results are attributable to the potent anti-oxidant and free radical scavenging properties of ARCE or EJSE reported in our earlier studies. 20,21 Mitochondrion is the most vulnerable organelle under oxidative stress which plays a key role in apoptosis. 36 Mitochondrial injury triggers its permeability resulting in release of cytochrome C into the cytosol, a critical initiation step in ROS induced triggering of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The total yield at the final step was 5.66% (w/w). 21 The total amount of flavonoids in EJSE was determined spectrophotometrically using quercetin as a standard. 23 Cell culture and treatment protocol.…”
Section: Preparation Of Anthocyanin Rich Red Cabbage Extract (Arce)mentioning
confidence: 99%
See 1 more Smart Citation
“…While the main flavonoid found in the pulp of S. cumini is anthocyanins, there are other important phytochemical constituents in the seeds of Jamun such as quercetin and rutin, and myricetin [ 57 ]. Among these compounds, quercetin, kaempferol, and rutin are mainly responsible for their effective bioactive potentials [ 71 ]. It is to be noted that the anthocyanins which are found in the fruit pulp are absent in the seeds, which might be affected during the ripening stage of the fruit [ 4 , 29 ].…”
Section: Clinical Effects Impartedmentioning
confidence: 99%